Tripodal Oxazolidine-N-Oxyl Diradical Complexes of Dy3+ and Eu3+ - Philippe Rey; Andrea Caneschi; Taisiya S. Sukhikh; Kira E. Vostrikova (Inorganics, 2021)
Two diradical complexes of the formula [LnRad2(CF3SO3)3] c (Ln(III) = Dy, Eu, Rad = 4,4-dimethyl-2,2-bis(pyridin-2-yl)-1,3-oxazolidine-3-oxyl) were obtained in air conditions. These are the first examples of diradical compounds of lanthanides and oxazolidine nitroxide. The complexes were characterized crystallographically and magnetically. Single crystal XRD analysis revealed that their coordination sphere is composed of three monodentate triflates and two tripodal Rad, which coordinate the central atom in a tridentate manner via two N atoms of the pyridine groups and the O atom of a nitroxide group. The LnO5N4 polyhedron represents a spherical capped square antiprism with point symmetry close to C4v. The data of static magnetic measurements are compatible with the presence of two paramagnetic ligands in the coordination sphere of the metal.